Imaging Cellular Aerobic Glycolysis using Carbon Dots for Early Warning of Tumorigenesis. Issue 1 (27th November 2020) - Li, Jipeng; Yang, Siwei; Liu, Zeyang; Wang, Gang; He, Peng; Wei, Wei; Yang, Muyue; Deng, Yuan; Gu, Ping; Xie, Xiaoming; Kang, Zhenhui; Ding, Guqiao; et al.
Abstract: Early warning of tumor formation is crucial for the classification, treatment, and prognosis of tumor patients. Here, a new strategy is reported, aimed at realizing this goal based on imaging aerobic glycolysis processes using nitrogen‐doped carbon dots (N‐CDs) as fluorescent probes. The intensity of the photoluminescence emitted by the N‐CDs is specifically enhanced by nicotinamide adenine dinucleotide (NAD +, oxidized) in the physiological environment. The N‐CDs allow a few (five to ten) abnormal cells in spontaneous hepatocellular carcinoma models to be identified before the in situ development of tumor tissue. The N‐CD probes can also distinguish tumor cells from normal cells and be used to evaluate their proliferation activity (with a specificity of up to 96.15% in 13 types of tumor cells and 90.90% in orthotopic xenograft models). The N‐CDs are successfully used to monitor the invasion of tumor cells into neighboring tissues and body fluids in 49 clinical samples (with a sensitivity up to 79.31%). These included three vitreous body samples (from patients with retinoblastoma), 42 urine samples (22 patients clinically diagnosed with urothelium carcinoma and 20 healthy persons), and four hydrothorax samples (from patients with metastatic lesions). Abstract : The occurrence of aerobic glycolysis based on nicotinamide adenine dinucleotide (NAD)‐induced enhancement of fluorescence emitted by nitrogen‐doped carbon dots is revealed by a new strategy. This can be used to monitor the occurrence of tumorigenesis and provide an early warning of tumor formation with high accuracy and specificity.